2008
DOI: 10.1038/nature07207
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference screen for human genes associated with West Nile virus infection

Abstract: West Nile virus (WNV), and related flaviviruses such as tick-borne encephalitis, Japanese encephalitis, yellow fever and dengue viruses, constitute a significant global human health problem1. However, our understanding of the molecular interaction of WNV (and related flaviviruses) with mammalian host cells is limited1. WNV encodes only 10 proteins, implying that the virus may use many cellular proteins for infection1. WNV enters the cytoplasm through pHdependent endocytosis, undergoes cycles of translation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
500
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(525 citation statements)
references
References 35 publications
17
500
2
1
Order By: Relevance
“…An important association independent from energy or metabolic homeostasis was identified for SLC16A4 , which encodes for MCT5 (formerly referred to as MCT4), with West Nile virus infections 74. In an in vitro RNA interference screen to investigate virus host cell interactions, knockdown of SLC16A4 was demonstrated to enhance West Nile virus infection.…”
Section: Ophthalmological Diseasesmentioning
confidence: 99%
“…An important association independent from energy or metabolic homeostasis was identified for SLC16A4 , which encodes for MCT5 (formerly referred to as MCT4), with West Nile virus infections 74. In an in vitro RNA interference screen to investigate virus host cell interactions, knockdown of SLC16A4 was demonstrated to enhance West Nile virus infection.…”
Section: Ophthalmological Diseasesmentioning
confidence: 99%
“…Indeed, recent application of the GSB approach to the analysis of animal-virus interactions has revealed new and interesting insights. For example, thoughtful statistical analyses of expression data has facilitated identification of virus-regulated genes (VRGs), some of which encode cellular factors required for completion of the infection cycle, while others are direct targets that the virus manipulates to deactivate the cell defense mechanisms [9,[12][13][14]. It has also been observed that VRGs are preferentially highly connected elements in the host regulatory network [15,16,17••].…”
Section: The Systems Biology Approachmentioning
confidence: 99%
“…The advent of siRNA technology and the availability of genome-wide siRNA libraries have been useful in identifying host factors required for influenza virus, an NS RNA virus, and several positive-strand RNA viruses, as well as HIV (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The lack of similar studies with other NS RNA viruses has limited the understanding of the role of host cell factors in replication of these viruses.…”
mentioning
confidence: 99%